Uncertainty About the Persistence of Inflation - Nicolas Pinkwart (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2010)
This paper offers several contributions to actual research and discussion on monetary policy. It clarifies the relationship between uncertainty of inflation persistence and optimal monetary policy and discusses the consequences of the recent Blanchard proposal to implement a higher inflation target in the light of parameter uncertainty. Furthermore, it provides insights of general interest on the methodological level by analyzing the interrelations between normalization of variables and their independence properties and by extending standard solution methods of dynamic programming problems to non-orthogonal parameter uncertainty.
Keywords: E52; E58; C61; 330; Inflation Persistence; Parameter Uncertainty; Inflation Target; Dynamic Programming; Inflation; Hysteresis; Risiko; Geldpolitik; Inflation Targeting; Dynamische Optimierung; Theorie